Analyzing Email Communication Patterns Among Bachelor of Information and Communication Technology Education (BICTE) Students: A Case Study - Ghimire, Nawaraj (Innovative Research Journal, 2023)
This study explores the difficult scenery of email communication between undergraduate students enrolled in the Bachelor of Information and Communication Technology Education (BICTE) program within the university. The research explores various facets of email usage, including structure, literacy, and performance, shedding light on the prevalent challenges faced by students in effectively conveying messages. Significant findings encompass issues such as inapt structure, the absence of vital information, empty subjects, casual language, and the tendency to send multiple emails at once. Through the analysis of 175 actual emails exchanged between students and department heads, the study seeks to unravel patterns, trends, and deficiencies in email communication. The identified challenges underscore the importance of enhancing digital literacy and communication skills among BICTE students, addressing the delicate balance between formality and informality in academic emails, and promoting organized correspondence to facilitate a positive and efficient learning environment. The insights gleaned from this research aim to inform strategic improvements in communication training within the BICTE program, ultimately fostering a more effective and professional email communication culture.